Improving the security and quality of real-time multimedia transmission in cyber-physical-social systems. (November 2018) - Sun, Qindong; Cao, Han; Qi, Wenjing; Zhang, Jingpeng
Real-time multimedia transmission from smart physical terminals usually meets the challenges of quality and security problems in cyber physical social systems, such as in the Internet of things systems, social network, and industrial Internet of things. The quality of real-time video transmission is often disturbed by the instability of cyber-physical-social systems, and the security of real-time video can be compromised if fake contents are embedded into the video during the transmission. According to the video coding information and the conditions of cyber-physical-social systems like mobile network, we design a sliding window scheme to solve the out-of-order and loss problems and thus improve the quality of real-time video. In the scheme, the key video frame can be retransmitted in a dynamic range of sliding window. The scheme also simplifies the process of packet sorting and can quickly complete the process of unpacking and playing of the video stream with high accuracy. To defend the attack of inserting fake video into real-time video, we also design a detection algorithm based on time-related token. The experimental results show that the proposed methods can guarantee the continuity of video stream, improve the quality of image in the mobile network and ensure the security during transmission effectively.